ChemInform Abstract: Aerobic Linear Allylic C—H Amination: Overcoming Benzoquinone Inhibition. Issue 29 (29th June 2016) - Pattillo, Christopher C.; Strambeanu, Iulia I.; Calleja, Pilar; Vermeulen, Nicolaas A.; Mizuno, Tomokazu; White, M. Christina
Abstract: Aerobic linear allylic amination reactions of terminal olefins using an O2 /Co/catalytic dihydroquinone redox relay in combination with a Pd/bis‐sulfoxide catalyst are investigated.